Metabolic improvement with short‐term, glucagon‐like peptide‐1 receptor agonist treatment does not improve cardiac diastolic dysfunction in patients with type 2 diabetes: A randomized, double‐blind, placebo‐controlled trial. Issue 10 (26th July 2021) - Bojer, Annemie Stege; Sørensen, Martin Heyn; Bjerre, Jenny; Gæde, Peter; Vejlstrup, Niels; Madsen, Per Lav
Abstract: Aim: To investigate if short‐term treatment with liraglutide, a glucagon‐like peptide‐1 receptor agonist, improves left ventricular diastolic function. Materials and Methods: An investigator‐initiated, double‐blind, randomized, placebo‐controlled trial on the effect of 18 weeks of treatment with liraglutide on diastolic function was assessed in patients with type 2 diabetes with signs of diastolic dysfunction (echo‐Doppler determined E/e' ≥ 9 and/or lateral e' ≤ 10 cm/s). Primary outcomes were improved left ventricle filling (the early peak filling rate [ePFR]) and left atrium ease of emptying (the passive emptying fraction [LAPEF ]), assessed by cardiac magnetic resonance imaging at rest and during chronotropic stress. Secondary outcomes included left ventricular and left atrial volumes and systolic function, measures of aortic stiffness and echocardiographic diastolic variables. Results: Forty patients were randomized to liraglutide subcutaneously 1.8 mg/day (n = 20) or placebo (n = 20). Liraglutide reduced HbA1c (−0.47%, 95% CI [−0.88% to −0.06%] [−5.1, 95% CI −9.7 to −0.62 mmol/mol]) and weight (−2.9, 95% CI [−4.6 to −1.2] kg); both P < .03. Liraglutide did not change ePFR at rest (−24 ± 60 vs. −6 ± 46 mL/s), during stress (2 ± 58 vs. −2 ± 38 mL/s), or the changes from rest to stress (12.9 ± 72.5 vs. 4.7 ± 104.0; all P > .05). LAPEF decreased with liraglutide during stress (−3.1% [−9.0%, 1.1%] vs. 1.0% [−2.9%, 6.1%]; P = .049), but no changes were evident at rest (−4.3% [−7.9%, 1.9%] vs. −0.6% [−3.1%, 2.2%]; P = .19), or for the changes from rest to stress (−1.7 ± 8.4 vs. 0.8 ± 8.2; P = .4). Secondary outcomes were unchanged by liraglutide. Conclusions: Short‐term treatment with liraglutide did not improve left ventricular diastolic function, suggesting the cardioprotective effect is not exerted through the improvement in diastolic dysfunction.